Anxiety and Depression Among People Under the Nationwide Partial Lockdown in Vietnam - Huong Thi Le; Andre Jun Xian Lai; Jiaqian Sun; Men Thi Hoang; Men Thi Hoang; Linh Gia Vu; Hai Quang Pham; Hai Quang Pham; Trang Ha Nguyen; Trang Ha Nguyen; Bach Xuan Tran; Bach Xuan Tran; et al. (Frontiers Media S.A., 2020)
This study aimed to evaluate the psychological effects of the partial lockdown on the people in Vietnam during the COVID-19 pandemic. An online questionnaire regarding attitudes toward COVID-19 along with psychological parameters, including the Impact of Event Scale-Revised (IES-R) Depression, Anxiety, Stress Scale-21 (DASS-21) was conducted. From a total of 1,382 questionnaires, the respondents reported low prevalence of depression (4.9%), anxiety (7.0%), and stress (3.4%). The mean DASS-21 scores recorded were also markedly lower compared to similar studies conducted in China, Italy, and Iran. Respondents who reported severe PTSD had significantly higher depression, anxiety, and stress levels. Factors that were associated with an increased level of depression, stress, and anxiety were being single, separated, or widowed, a higher education level, a larger family size, loss of jobs and being in contact with potential COVID-19 patients. Contrary to expectations, the level of depression, stress, and anxiety observed has been low. Our findings can aid in future research on the impact of a partial lockdown and guide mental health professionals in Vietnam and other countries in the preparation of better care for populations under such circumstances.